Correcting Coagulopathy for Image-Guided Procedures - Novelli, Paula M.; Tublin, Joshua M.; Orons, Philip D. (Seminars in Interventional Radiology, 2022)
Patients with acquired coagulopathy often require percutaneous image-guided invasive procedures for urgent control of hemorrhage or for elective procedures. Routine preprocedural evaluation of coagulopathy previously focused on absolute prothrombin time, partial thromboplastin time, international normalized ratio, and platelet count values. Now viscoelastic testing and greater understanding of patient- and drug-specific changes in coagulation profiles can yield better coagulation profile data. More specific reversal agents and profiles combine for less generalized and more titrated transfusion or correction algorithms. This article reviews procedural and patient-specific factors for defining both hemorrhagic risk and correction strategies.
Keywords: interventional radiology; coagulopathy; hemorrhage; hemostasis; clotting disorders